1995
DOI: 10.1006/viro.1995.9931
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Type 11 E1 up angle E4 and L1 Proteins Colocalize in the Mouse Xenograft System at Multiple Time Points

Abstract: The most abundant viral mRNA species in HPV 11-infected tissue consists of two exons, joining a segment of open reading frame (ORF) E1 to ORF E4, potentially encoding the E1--E4 protein. The L1 ORF encodes the major capsid protein of HPV. Our previous studies demonstrated colocalization of the HPV 11 E1--E4 and L1 proteins within the same cells of HPV 11-infected human foreskin implants grown in athymic mice (the mouse xenograft system) and removed 12 weeks after implantation. Prior studies have demonstrated E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
0
12
1
1
Order By: Relevance
“…Xenografts propagated under the kidney capsule, however, did show a lower degree of papillomatosis than lesions produced at the natural site of infection, as reported previously (8). It appears that L1 expression always follows that of E4, in contrast to previous reports, which have indicated that the expression of E4 and L1 is coincident (18,20). HPV11 xenografts propagated on the skin (in SCID mice) showed similarity to naturally occurring human genital lesions both in their morphology and in their pattern of late gene expression (compare Fig.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…Xenografts propagated under the kidney capsule, however, did show a lower degree of papillomatosis than lesions produced at the natural site of infection, as reported previously (8). It appears that L1 expression always follows that of E4, in contrast to previous reports, which have indicated that the expression of E4 and L1 is coincident (18,20). HPV11 xenografts propagated on the skin (in SCID mice) showed similarity to naturally occurring human genital lesions both in their morphology and in their pattern of late gene expression (compare Fig.…”
Section: Resultscontrasting
confidence: 58%
“…Several papillomaviruses, including ROPV (28), CRPV (30), and HPV11 (36,63), can be propagated in epithelial tissue implanted under the renal capsule. This approach has been used to generate stocks of animal (28) and human papillomaviruses and to study the HPV life cycle in vivo (18,20). Renal-capsule xenografts infected with CRPV or ROPV were compared to experimental infections in their natural hosts with regard to the timing of initiation of late events described above.…”
Section: Resultsmentioning
confidence: 99%
“…BamHI-digested DNA was recircularized by intramolecular ligation, and recircularized DNA was recovered with a QIAGEN spin column (QIAprep Spin Miniprep kit; QIAGEN, Valencia CA). The recovered DNA was cotransfected with 1.2 g of pEGFP-N1 (BD Bioscience Clontech, Palo Alto, CA) into 3 ϫ 10 5 NIKS cells that were prepared in low Ca 2ϩ F medium without feeder cells as previously described (19,23). G418 selection was performed for 4 days as follows: 100 g/ml for 2 days and then 50 g/ml for next 2 days.…”
Section: Construction Of E4 Mutant Hpv16 Genomesmentioning
confidence: 99%
“…Although the human epithelium xenograftimmunocompromised mouse system has been successfully developed to study HPV-11 production and the molecular events associated with the pathogenesis of wart formation, there are some limitations in applying this animal model to screen and evaluate anti-HPV agents due to its complexity in operation and time-consuming process. [5][6][7] The complete life cycles of all HPVs are strictly regulated by the differentiation program of infected epithelial cells, which are divided into early stages and virus-productive stages. 8 After HPVs invade the epithelium through skin wounds, the early stage of the life cycle of HPVs occurs in the proliferating basal-layer cells.…”
Section: Research-article2014mentioning
confidence: 99%